Training in the creation of interactive read-aloud video books as a medium for children's digital literacy - Fadillah Sandy; Hikmawati Fajri Devi Safitri; Abiandra Aly Pramudya; Rika Yulia Irianti; Gamala Risfie Al Mahmmud; Muhammad Jody Alfaiyed (Universitas Muhammadiyah Magelang, 2021)
Literacy has not become a flagship program at the PKK of Grabag District. However, literacy problems in this group are quite complex related to the lack of literacy facilities, lack of literacy movement assistance, and the tendency of gadget addiction which makes literacy culture quite worrying. Community empowerment for PKK members in Grabag District aims to provide training and assistance in the creation of interactive read-aloud with a video book concept that can be used as a digital literacy media, especially for children. The training was carried out 4 times and video-making assistance was conducted 1 time online. The speakers who attended were interactive read-aloud practitioners, librarians, founder of Taman Baca, and the Unimma student team with 11 participants from PKK representatives in Grabag District. As a result, 4 video books have been created by participants and published on social media.